Designer lignins: harnessing the plasticity of lignification. (February 2016) - Mottiar, Yaseen; Vanholme, Ruben; Boerjan, Wout; Ralph, John; Mansfield, Shawn D
Graphical abstract: Highlights: Plant lignification is highly plastic. Designer lignins may satisfy biological requirements while reducing recalcitrance. Engineered lignins may be shorter, less hydrophobic, or have fewer bonds to hemicelluloses. Novel chemically labile backbone bonds in lignin may be easily cleaved during processing. Lignins could be designed to produce high-value products. Abstract : Lignin is a complex polyphenolic constituent of plant secondary cell walls. Inspired largely by the recalcitrance of lignin to biomass processing, plant engineering efforts have routinely sought to alter lignin quantity, composition, and structure by exploiting the inherent plasticity of lignin biosynthesis. More recently, researchers are attempting to strategically design plants for increased degradability by incorporating monomers that lead to a lower degree of polymerisation, reduced hydrophobicity, fewer bonds to other cell wall constituents, or novel chemically labile linkages in the polymer backbone. In addition, the incorporation of value-added structures could help valorise lignin. Designer lignins may satisfy the biological requirement for lignification in plants while improving the overall efficiency of biomass utilisation.